A study of the community school in Bulacan - Payaual, Rafael B. 1910- (1955)
This study attempted to reveal how much the community school really has achieved in helping the people of Bulacan improve their ways of living. It showed the phases of work that the movement has been successful at. It also showed how much the community school in Bulacan helped the people in uplifting the condition of living in rural areas.
Mimeographed.
Vita.
Thesis (M.A.)--University of the Philippines, Diliman.
Keywords: Education -- Philippines -- Bulacan